2016
DOI: 10.15412/j.bcn.03070307
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Craving in Methamphetamine Abuse

Abstract: Introduction:Methamphetamine is a powerful psychostimulant that causes significant neurological impairments with long-lasting effects and has provoked serious international concerns about public health. Denial of drug abuse and drug craving are two important factors that make the diagnosis and treatment extremely challenging. Here, we present a novel and rapid noninvasive method with potential application for differentiation and monitoring methamphetamine abuse.Methods:Visual stimuli comprised a series of imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In methamphetamine consumers, increased P3 amplitudes to drug-related pictures (Shahmohammadi et al 2016) and words (Haifeng et al 2015) have been detected at the beginning of a therapy. With increasing duration of abstinence, P3 amplitudes normalised suggesting treatment success.…”
Section: P3mentioning
confidence: 99%
“…In methamphetamine consumers, increased P3 amplitudes to drug-related pictures (Shahmohammadi et al 2016) and words (Haifeng et al 2015) have been detected at the beginning of a therapy. With increasing duration of abstinence, P3 amplitudes normalised suggesting treatment success.…”
Section: P3mentioning
confidence: 99%
“…Blood-oxygen-level dependent measures of methamphetamine cue reactivity revealed activation of a broad set of regions, particularly the mesocorticolimbic system which includes the ventral and dorsal striatum, the cingulate cortex, prefrontal cortex (PFC) and insula [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Two studies looked at EEG recordings: one study utilized event-related potential (ERP) technique and found higher neural responses to drug-related visual stimuli among users compared to controls in the P300 components [ 36 ], while the other study measured gamma current density and found gamma activity in medial prefrontal cortex (mPFC)/orbitofrontal cortex (OFC) and right dorsolateral prefrontal cortex (DLPFC) to decrease after cue exposure [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 images related to methamphetamine were selected from images that were validated in previous studies ( Ekhtiari, Alam-Mehrjerdi, Nouri, George, & Mokri, 2010 ; Shahmohammadi et al, 2016 ). Each cue image was paired with a neutral image, and each pair was matched in semantic content and resolution as closely as possible.…”
Section: Methodsmentioning
confidence: 99%